FRAMING ANALYSIS OF DEMONSTRATION NEWS IN NU ONLINE - N. Rosidah, (Proceeding International Conference on Islam and Civilization (ICONIC), 2026)
This study examines how NU Online constructs news about waves of demonstrations by student activists and civil society groups in Jakarta and surrounding areas related to the House of Representatives (DPR) promises, performance, and the controversy over a significant increase in members’ allowances. Using a descriptive qualitative approach, the research applies Zhongdang Pan and Gerald M. Kosicki’s framing analysis model, which analyzes four framing structures: syntactic, script, thematic, and rhetorical. The data consist of NU Online news texts published between August 25 and September 10, 2025, selected purposively from national news coverage and analyzed through source triangulation. The findings show that NU Online’s syntactic structure tends to foreground escalation and tension, portraying demonstrations as marked by chaos, arrests, injuries, and fatalities. In the script structure, NU Online emphasizes “what,” “who,” and “why” elements to connect events to public concerns and to highlight demands voiced by demonstrators. The thematic structure consistently details protesters’ aspirations and the dynamics of confrontation with security forces, framing the demonstrations as a struggle for justice and accountability. In the rhetorical structure, NU Online strengthens meaning through assertive diction and repeated keywords such as “murderer,” “condemn,” “denounce,” and “demand,” which intensify moral judgment and emphasize calls for protection of civil rights. Overall, NU Online frames the demonstrations as a legitimate public alarm and a justice-seeking movement, while also highlighting the consequences of repression and the need for independent investigation and resolution.